Complicating the Narrative about Emergency Certified Special Educators. Issue 5 (20th October 2022) - Wilkerson, Kimber L.; Sikora, Elizabeth E.; Leko, Melinda M.
ABSTRACT: For decades, school districts have relied on unlicensed teachers to fill vacancies in special education, leaving students with disabilities to receive educational services from individuals without the necessary preparation, resulting in inequitable educational opportunities. An emergency certification, granted in numerous states, allows unlicensed teachers to provide students' instruction. We utilized teacher licensure data from a state education agency to examine the preparation pathways of emergency certified special educators in one Midwestern state. Through our descriptive analysis of 798 special educators, 62.5% obtained a full special education teaching license. Traditional educator preparation programs (50.4%) and alternative programs (48.9%) were completed at comparable rates, and special educators worked most frequently on an emergency certification for one year before obtaining full licensure. We provide implications for future research and practice to increase students' access to qualified special educators.